Scholarship of education and human rights in diversity Engaging discourses from the South - Wolhuter, Charl C. (NWU Education and Human Rights in Diversity, 2022)
The objective of this book is to highlight the need and value of imbuing the dynamic intersections between education, human rights and diversity with perspectives from the Global South. The chapters approach key intellectual conundrums of the day from a Global South perspective to reflect a credible scholarly footprint in Africa and in the SADC region. This is deemed timely considering that the field is deeply embedded in western, Eurocentric and overall Global North dominance. This book will provide a Southern perspective on education and human rights in diversity by unpacking each of the following key areas in the intersection between education, human rights and diversity from a Southern perspective: comparative international perspectives, citizenship education, human rights literacies, human rights education pedagogy, learner discipline in schools, aggression and bullying in schools, addressing human trafficking by means of human rights education, social justice, and the decolonisation of human rights and human rights education.